382 INTRATHORACIC VERSUS CERVICAL ANASTOMOSIS AFTER MINIMALLY INVASIVE ESOPHAGECTOMY FOR OESOPHAGEAL CANCER: A RANDOMIZED CONTROLLED TRIAL (ICAN TRIAL). (17th September 2021) - Verstegen, Moniek; Workum, Frans; Klarenbeek, Bastiaan; Bouwense, Stefan; Gisbertz, Suzanne; Haveman, Jan Willem; Heisterkamp, Joos; Kouwenhoven, Ewout; Lanschot, Jan; Nieuwenhuijzen, Grard; Peet, Donald; Polat, Fatih; et al.
Abstract: : Robust evidence is lacking whether Ivor Lewis minimally invasive esophagectomy (MIE) or McKeown MIE should be preferred for patients with mid to distal esophageal or gastro-esophageal junction Siewert I-II (GEJ) cancer. Methods: In this multicenter randomized controlled trial, patients with esophageal (below the level of the carina) or GEJ cancer planned for curative resection were recruited. Eligible patients were randomly assigned (1:1) to either Ivor Lewis MIE or McKeown MIE. The primary endpoint was anastomotic leakage (AL) requiring endoscopic, radiologic or surgical intervention. Secondary outcome parameters were overall AL rate, postoperative complications, length of stay and mortality. Results: A total of 262 patients were randomly assigned to Ivor Lewis MIE (n = 130) or McKeown MIE (n = 132). Seventeen patients were excluded due to not meeting inclusion criteria (n = 2), physical unfitness for surgery (n = 3), patients' choice (n = 3), interval metastases (n = 5) or peroperative metastases (n = 4). AL necessitating reintervention occurred in 15 (12.3%) of 122 patients after Ivor Lewis MIE and in 39 (31.7%) of 123 patients after McKeown MIE (RR 0.39, 95%CI 0.22–0.65). Severe complications (Clavien-Dindo ≥3b) were observed in 10.7% after Ivor Lewis MIE and in 22.0% after McKeown MIE (RR 0.49, 95%CI 0.25–0.88). Conclusion: This study provides evidence for a lower rate of AL requiring reintervention after Ivor Lewis MIE compared to McKeown MIE for patients with mid to distal esophageal or GEJ cancer.